A biomechanical comparison of track spikes with advanced footwear technology to a traditional track spike in female distance runners - Geisler, C.; Hannigan, J. J. (Sports Biomechanics, 2024)
The addition of highly responsive lightweight foam and a stiff plate in the midsole of long-distance road racing shoes has yielded significant energetic cost savings that have translated to notable improvements in performance. This new foam and stiff plate technology have since been implemented in long-distance track spikes, where performances have also improved. However, the impact of spikes with advanced footwear technology (AFT) on distance running biomechanics has been studied minimally to date. Therefore, the purpose of this study was to compare running biomechanics between two spikes which incorporate AFT (Nike ZoomX Dragonfly, Nike Air Zoom Victory) to a traditional spike (Nike Zoom Matumbo). Seventeen competitive collegiate female runners completed 60 m trials at their 5k race pace in each spike condition while outfitted with IMU sensors and plantar pressure insoles. We observed significantly lower peak ankle dorsiflexion in the Dragonfly and Victory compared to the Matumbo and lower whole foot, forefoot and rearfoot peak and average pressure in the Dragonfly compared to the Matumbo and Victory. The acute biomechanical alterations observed in this study warrant future investigation into the association between running biomechanics and racing performance in track spikes with advanced footwear technology.